UPI-BASED SMART SANITARY NAPKIN VENDING MACHINE - Dr. Pradeep Karanje; Udaytada Malle; Somshekar Patil; Srikanthha Milpurkar; Omkar Surywanshi (International Educational Journal of Science and Engineering, 2026)
Menstrual hygiene remains a pressing concern, particularly in regions where access to sanitary products is limited by affordability, availability, and social stigma. This paper introduces a UPI-based smart sanitary napkin vending machine designed to provide secure, cashless, and user-friendly solution for product distribution. By integrating India’s Unified Payments Interface (UPI), the system enables instant digital transactions through QR code scanning, eliminating the need for physical currency and simplifying access. The vending machine employs micro controller-driven dispensing mechanism, supported by sensors to monitor stock levels and operational status. Its IoT-enabled design ensures reliability, predictive maintenance, and scalability for deployment in schools, workplaces, and public facilities. Beyond technical efficiency, the system addresses cultural sensitivities by automating distribution, thereby reducing human interaction. Pilot testing demonstrates efficient dispensing, secure payment processing, and positive user feedback. The proposed solution offers a sustainable, scalable, and socially impactful approach to menstrual hygiene management.